Exploring Teachers’ Perception on Project Based Learning (PJBL) in Teaching Speaking of Report Text at Junior High School - Pertiwi, Nestiti Lintang; Nurhayati, Dwi Astuti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
At the junior high school level, the ability to speak English, especially in the form of report text, is an important focus in the curriculum. One innovative learning method that is widely applied at various levels of education is Project Based Learning (PjBL). Using PjBL in learning can contribute to supporting the teaching and learning process and developing students' speaking skills. This research explores teachers' perspectives regarding implementing Project-Based Learning (PjBL) in teaching speaking report text. The focus of this research is to understand teachers' perceptions of the implementation of PjBL in speaking skills, their approach to planning, implementing, and assessing PjBL, as well as the benefits and challenges they face. Data for this study was gathered through interviews and documentation using the case study methodology. The results showed that teachers believed that PjBL increased student engagement, provided real-world experience, increased motivation, and allowed peer-feedback. PjBL implementation includes three main stages: planning, implementation, and assessment. The benefits identified from implementing PjBL include improving students' pronunciation skills, vocabulary knowledge, creativity, and self-confidence. However, challenges include limited time allocation, diverse student learning styles, and uneven student participation. These findings can contribute to educators optimizing the use of PjBL to improve students' speaking abilities.